Dating Violence: An Overview of Help-Seeking Behavior, Trust in Authority, and Peer Support - Fathul Lubabin Nuqul; Iin Tri Rahayu (Psympathic : Jurnal Ilmiah Psikologi, 2022)
Dating violence is increasing every day and continues to constitute a social problem. Students are a social group with the highest risk of becoming victims. Furthermore, not all victims are willing to report these cases. Previous studies show that victims of dating violence are reluctant to report it as they may not receive good treatment. This study aims to explore the forms of dating violence, victims, directions for seeking help, trust in campus authorities, peer support, and intercorrelations. It involves a correlational quantitative method with 225 students taken based on purposive random sampling. This study also uses a scale of conflict in dating, friend support, choice of support, and trust in authority. The results showed that most of the violence experienced by victims is psychological. Victims tend to seek help from informal parties such as friends, family, and partners, instead of formal parties such as doctors, psychologists, police, or lecturers. Trust in campus authorities tends to be moderate, and the majority feel support from friends. Furthermore, positive and negative correlations were observed between the variables and their dimensions.